Dyslipidemia in insulin dependent diabetic children - Shemkhi Jebr, Mehdi; Najm Abed, Baraa; Adnan Hussein, Huda (Diyala Journal of Medicine, 2024)
Background: Children and adolescents with insulin-dependent diabetes mellitus (IDDM) are at high risk of metabolic disorders that may interfere with lipid metabolism and predispose to dyslipidemia. Objective: To detect the incidence of dyslipidemia and associated factors in children with IDDM in Diyala. Patients and Methods: This was a case-control study that included a total of 100 children with type 1 diabetes mellitus(T1DM) and 100 age- and gender-matched non-diabetic children who presented to the Pediatric Department/Al-Batool Teaching Hospital during the period from April 2022 to April 2023. Demographic data included the child's age, gender, weight, mother’s educational level, mother's job, child's educational level, school attendance, and physical activity. Clinical data included systolic and diastolic blood pressure, HbA1c, family history of illness, disease duration, type of insulin, and insulin dose. Fasting lipid profile and hemoglobin A1c investigations were done for the study groups, and the data were statistically analyzed. Results: The overall dyslipidemia in IDDM children and controls was 46% and 8%, respectively, with a highly significant difference. The mean age and weight in diabetic patients with dyslipidemia were 8.23±3.63 years and 28.96±13.31 kg, respectively, which was higher than that of normolipidemic diabetic patients (10.72±3.23 years and 34.22±12.14 kg, respectively) with significant differences. Furthermore, 28.26% of mothers of dyslipidemia-.diabetic patients were employed, compared with only 11.11% of normolipidemic-diabetic patients, a significant difference. A family history of DM was reported in 47.83% and 27.78% of dyslipidemic and normolipidemic diabetic patients, respectively, with a significant difference. Conclusion: The incidence of dyslipidemia among diabetic children in Diyala is 46%. Older age, increased body weight, and a mother’s job as an employer are significantly associated with the development of dyslipidemia in insulin-dependent diabetes mellitus patients.